Church (16099097160) - Miami University... (Wikimedia Commons, 2015)
Carte postale ancienne issue de Wikimedia Commons. Titre: Church (16099097160). Persistent URL: digital.lib.miamioh.edu/cdm/compoundobject/collection/pos... Subject: World War I | Lost architecture | Churches | War damage | France–La Chavatte | miami digital collections | bowden postcard collection
Licence No known copyright restrictions via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église